Investigating the Therapeutic Mechanisms of Total Saikosaponins in Alzheimer’s Disease: A Metabolomic and Proteomic Approach - Huiling Wei; Tianyi Du; Weiwei Zhang; Wei Ma; Yao Yao; Juan Li (Pharmaceuticals)
Alzheimer’s disease (AD) is the leading cause of dementia among the elderly, yet effective treatments remain elusive. Total saikosaponins (TSS), the primary bioactive components in Bupleurum chinense, have shown promising therapeutic effects against AD in previous studies. Methods: To delve deeper into the mechanisms underlying the therapeutic role of TSS in AD, we investigated its neuroprotective effects and associated molecular mechanisms in APP/PS1 mice. Further, we employed metabolomic and proteomic analyses, with a focus on the potential protein-level changes induced by TSS, particularly those related to metabolite accumulation in the brain. Results: Our results showed that lysophosphatidylcholine, adenosine, and sphingomyelin in plasma might serve as potential biomarkers. Compared to the control group, AD mice exhibited significantly increased expression of proteins related to neuroinflammatory pathways, whereas proteins involved in cAMP signaling, cGMP-PKG signaling, and synaptic plasticity pathways were significantly downregulated. Notably, these signaling pathways were partially reversed in APP/PS1 mice following TSS administration. Behavioral tests demonstrated that TSS effectively improved the learning and memory functions of mice. Conclusions: Our findings suggest that TSS ameliorate cognitive decline through regulating neuroinflammatory pathways, cAMP and cGMP signaling, and synaptic plasticity pathways, providing insights into its therapeutic potential in AD.